Quiero Creedence [compact disc]. - Bunbury, Enrique; Gabriel, Juan; Calamaro, Andrés; Santana, Salvador, 1983-; Juanes; Sierra, Asdru; Gibbons, Billy F., 1949- (Concord Picante, 2016)
Latin music tribute to the rock band Creedence Clearwater Revival.